How do crises affect schooling decisions? Evidence from changing labor market opportunities and a policy experiment - Florencia López Bóo (Inter-American Development Bank, Research Department, 2008)
This paper examines the effect of labor market opportunities on schoolingemployment decisions in 12 urban areas in Argentina over 12 years, emphasizing the recession/crisis years 1998-2002. Over 'typical' years deteriorating job rates increase the probability of attending school and decrease the probability of combining work and school, particularly for boys; the probability of being in school for secondary school children was about 6 percent higher in 2002 than in 1998. These estimates account for the fact that a new Federal Education Law (FEL) in 1996 extended mandatory education to 10 years. Differences across regions in implementation and differences in exposure across cohorts induced by the timing of the Law reveal that children in provinces fully implementing the FEL were 3 percent more likely to be in school and 1.6 percent points less likely to be working.
Keywords: I21; J31; 330; schooling decision; macroeconomic shocks; education policy; Bildungsverhalten; Schule; Bildungspolitik; Arbeitsmarkt; Schock; Finanzmarktkrise; Schätzung; Argentinien